Interleukin-17 induces human alveolar epithelial to mesenchymal cell transition via the TGF-β1 mediated Smad2/3 and ERK1/2 activation. - Ting Wang; Yuan Liu; Jing-Feng Zou; Zhen-Shun Cheng (PLoS ONE)
Idiopathic pulmonary fibrosis (IPF) is a chronic and usually progressive lung disease and the epithelial-mesenchymal transition (EMT) may play an important role in the pathogenesis of pulmonary fibrosis. IL-17 is a proinflammatory cytokine which promotes EMT profiles in lung inflammatory diseases. In this study, we investigated the effect of IL-17 on EMT in alveolar epithelial cell line A549 and the role of TGFβ1-Smad and ERK signaling pathways in the process. Morphological observation on the cells was performed under inverted microscope. The mRNA and protein expressions of E-cad and α-SMA were detected by quantitative RT-PCR and western blotting. The mRNA and protein expressions of TGF-β1 were analyzed via quantitative RT-PCR and ELISA. Expressions of Smad2/3, p-Smad2/3, ERK1/2, p-ERK1/2 and p-JNK were examined by western blotting. The results indicated that IL-17 can induce A549 cells to undergo morphological changes and phenotypic markers changes, such as down-regulated E-cad expression and up-regulated α-SMA expression. Additionally, IL-17 enhanced TGF-β1 expression and stimulated Smad2/3 and ERK1/2 phosphorylation in A549 cells. However, there were no significant differences in the expression of phosphorylated JNK in A549 cells with or without IL-17 treatment. SB431542 or U0126 treated cells showed inhibited morphological changes and phenotypic markers expression, such as up-regulated E-cad expression and down-regulated α-SMA expression. In summary, our results suggest that IL-17 can induce A549 alveolar epithelial cells to undergo EMT via the TGF-β1 mediated Smad2/3 and ERK1/2 activation.